2012
DOI: 10.17221/6313-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Dietary linseed oil and selenate affect the concentration of fatty acids in selected tissues of sheep

Abstract: ABSTRACT:The aim of the study was to determine the influence of the addition of 5% linseed oil (LO) and 2 µg Se as selenate (SeVI) per g of diet on body mass gain (BMG), feed conversion efficiency (FCE), and concentrations of fatty acids (FA), especially conjugated linoleic acid (CLA) isomers, in the liver, heart, m. longissimus dorsi (MLD), m. biceps femoris (MBF), subcutaneous fat (SF), perirenal fat (PF), and intermuscular fat (IF) of sheep. Each group comprised 5 lambs with an average initial body weight o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…Our previous study (RozbickaWieczorek et al, 2016c) also demonstrated that SeVI addition to diet containing 2% RO, 1% FO and CA decreased the capacity of carbohydrate fermentation into VFA and lipogenic enzymes in the lamb body, whereas stimulated the microorganism protein biosynthesis in the rumen. Moreover, the present data are in agreement with the results of Czauderna et al (2012), in which diet containing only SeVI reduced the concentration of ΣFA, especially ΣPUFA and ΣMUFA, in longissimus dorsi (LD) and biceps fermoris (BF) muscles of lambs in comparison to animals fed control diet or diet supplemented with linseed oil. Our recent investigations (Miltko et al, 2016) indicated that the lowest concentration of acetic acid in the ruminal fluid collected from lambs fed experimental diet with SeVI was associated with decreased biosynthesis yield of acetyl-CoA to lipids in lamb tissues.…”
Section: Discussionsupporting
confidence: 91%
“…Our previous study (RozbickaWieczorek et al, 2016c) also demonstrated that SeVI addition to diet containing 2% RO, 1% FO and CA decreased the capacity of carbohydrate fermentation into VFA and lipogenic enzymes in the lamb body, whereas stimulated the microorganism protein biosynthesis in the rumen. Moreover, the present data are in agreement with the results of Czauderna et al (2012), in which diet containing only SeVI reduced the concentration of ΣFA, especially ΣPUFA and ΣMUFA, in longissimus dorsi (LD) and biceps fermoris (BF) muscles of lambs in comparison to animals fed control diet or diet supplemented with linseed oil. Our recent investigations (Miltko et al, 2016) indicated that the lowest concentration of acetic acid in the ruminal fluid collected from lambs fed experimental diet with SeVI was associated with decreased biosynthesis yield of acetyl-CoA to lipids in lamb tissues.…”
Section: Discussionsupporting
confidence: 91%
“…The relative increase in the concentration of C20:5n-3 in the fluids with LO and Se, especially as Se IV H or Se VI H, was higher than the relative increase in the concentration of αLNA in the fluids with LO and the higher concentration of Se IV or Se VI . This effect should be observed in in vivo investigations, resulting in an enhanced duodenal flow of αLNA or C20:5n-3 (Niedźwiedzka et al, 2008;Czauderna et al, 2010Czauderna et al, , 2012bKrajewska et al, 2012). Our observations are also consistent with recent in vivo and in vitro studies that have reported that the ruminal biohydrogenation of C20:5n-3 and other LPUFAn-3 was significantly lower compared to the ruminal biohydrogenation of C18-PUFA (e.g., LA or αLNA) (Dohme et al, 2003;Chow et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…In fact, increasing contents of PUFAs, and especially n-3LPUFAs, in ruminant tissues is very important in view of the generally saturated nature of FAs in ruminant meats and the negative effect this can have on human health. Fortunately, amounts and types of fat and pro-or antioxidants added to the diet can influence the biohydrogenation yield of UFAs and the FA profiles in ruminant tissues (1,(4)(5)(6)(7). Our studies indicated that feeding linseed oil or FO effectively decreased the content of SFAs in tissues and increased the content of valuable monounsaturated FAs (MUFAs) and PUFAs (4).…”
Section: Introductionmentioning
confidence: 67%
“…Fortunately, amounts and types of fat and pro-or antioxidants added to the diet can influence the biohydrogenation yield of UFAs and the FA profiles in ruminant tissues (1,(4)(5)(6)(7). Our studies indicated that feeding linseed oil or FO effectively decreased the content of SFAs in tissues and increased the content of valuable monounsaturated FAs (MUFAs) and PUFAs (4). Moreover, our studies documented that FO is able to modify the biohydrogenation yield by decreasing the enzymatic isomerization capacity of linoleic acid (LA) or α-linolenic acid (αLNA) and simultaneously elevating the trans11C18:1 (t11C18:1) concentration in ruminal bacteria and tissues (1,2,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation